2016
DOI: 10.1002/hed.24588
|View full text |Cite
|
Sign up to set email alerts
|

Direct intralesional ethanol sclerotherapy of extensive venous malformations with oropharyngeal involvement after a temporary tracheotomy in the head and neck: Initial results

Abstract: Direct intralesional ethanol sclerotherapy after a temporary tracheotomy is a safe and effective treatment for extensive VMs involving oropharyngeal areas of the head and neck. © 2016 Wiley Periodicals, Inc. Head Neck 39: 288-296, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Neurological critical patients refer to those critical patients who need intensive care because of craniocerebral trauma, intracranial tumors, intracranial hemorrhage, aneurysms, and other diseases, after or without surgery [ 13 ]. Most of these patients have disturbance of consciousness because of their condition, and when patients have disturbance of consciousness, especially when GCS ≤ 8, the ability of spontaneous coughing and sputum is weakened and the root of tongue is more likely to fall back.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological critical patients refer to those critical patients who need intensive care because of craniocerebral trauma, intracranial tumors, intracranial hemorrhage, aneurysms, and other diseases, after or without surgery [ 13 ]. Most of these patients have disturbance of consciousness because of their condition, and when patients have disturbance of consciousness, especially when GCS ≤ 8, the ability of spontaneous coughing and sputum is weakened and the root of tongue is more likely to fall back.…”
Section: Discussionmentioning
confidence: 99%
“…Most included studies used a single sclerosing agent for each vascular malformation, while the remainder used a combination of them. Five studies reported outcomes of bleomycin sclerotherapy, 10 studies reported outcomes of ethanol sclerotherapy, 7 studies reported outcomes of STS sclerotherapy, 4 studies reported outcomes of ethanolamine 4 (2011) 0.409 (0.204, 0.615) Kishi et al 16 (2014) 0.979 (0.922, 1.036) Lamba et al 17 (2012) 0.286 (0.049, 0.522) Lee et al 18 (2009) 0.324 (0.215, 0.433) Orlando et al 22 20140.275 (0.152, 0.397) Spence et al 29 20110.972 (0.896, 1.048) Su et al 32 20100.933 (0.870, 0.996) Wang et al 33 20170.333 (0.132, 0.535) Wang et al 34 20 (2009) 0.391 (0.192, 0.591) Meng et al 21 20140.163 (0.052, 0.273) Songsaeng et al 28 20150.576 (0.407, 0.744) Zhao et al 35 sclerotherapy, and 4 studies reported outcomes of pingamycin sclerotherapy. In 11 studies either multiple agents were used and we could not separate outcomes by agent or other sclerosing agent including OK-432 were used.…”
Section: Literature Searchmentioning
confidence: 99%
“…El tipo de lesión suele estar presente al nacer y crece proporcionalmente con la edad. Aproximadamente el 40 % se desarrollan en regiones de cabeza y cuello (Miyazaki et al, 2014;Chen et al, 2015;Wang et al, 2017), suelen ser unilaterales, con un efecto de masa que causa una distorsión significativa y asimetría facial.…”
Section: Malformaciones Venosas (Mv)unclassified